Perception of duration in the parvocellular system - Cicchini, Guido Marco (Frontiers in Integrative Neuroscience, 2012)
Both theoretical and experimental evidence suggests that duration perception is mediated preferentially by the colour-blind but high temporally sensitive luminance pathway. In this experiment we tested whether colour modulated stimuli and high spatial frequency luminance modulated stimuli, which are known to be relayed mostly by the slow parvocellular system, are able to elicit reliable sense of duration. We show that ramped colour modulated stimuli seem to last less than luminance modulated stimuli matched for visibility. The effect is large, about 200 ms and is constant at all durations tested (range 500 - 1100 ms). However high spatial frequency luminance stimuli obtain duration matches similar to those of low spatial frequency luminance modulated stimuli. The results at various levels of contrast and temporal smoothing indicate that equiluminant stimuli have higher contrast thresholds to activate the mechanisms which time visual stimuli. Overall the results imply that both the magnocellular and the parvocellular systems access reliably the timing mechanisms with a difference only in the way these are engaged.